A case of partial trisomy 15. Issue 4 (December 1974) - Watson, E. Janet; Gordon, R. R.
Abstract : A girl with mental retardation but few distinctive physical abnormalities is described. Chromosome analysis revealed an extra small acrocentric chromosome with both long and short arms satellited which was identified as a deleted chromosome No. 15. The origin of this chromosome is discussed and the clinical findings compared with those of previously reported cases of partial trisomy 15.